2018
DOI: 10.1007/s12039-018-1537-x
|View full text |Cite
|
Sign up to set email alerts
|

Viable access to the triplet excited state in peryleneimide based palladium complex $$^{\S }$$ §

Abstract: Triplet excited state in organic chromophores is ubiquitously significant owing to its utility in light harvesting and photovoltaic device applications. Herein, we report the enhancement in the triplet character of an innately triplet deficient peryleneimide chromophore via incorporation of a heavy atom. Palladium incorporated perylenemonoimide (PMI-Pd) was synthesized via oxidative addition of PMI-Br into Pd(0) under inert experimental conditions. The structural sanctity of the PMI-Pd and the model derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Hariharan et al [ 59 ] studied how the incorporation of Pd affected the perylenemonoimide (PMI) chromophore 1 . They found that the incorporation of Pd was correlated with better access to triplet-excited states by ISC, associated with a greater spin–orbit coupling (SOC).…”
Section: Orthopalladated Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hariharan et al [ 59 ] studied how the incorporation of Pd affected the perylenemonoimide (PMI) chromophore 1 . They found that the incorporation of Pd was correlated with better access to triplet-excited states by ISC, associated with a greater spin–orbit coupling (SOC).…”
Section: Orthopalladated Ligandsmentioning
confidence: 99%
“… Jablonski diagram depicting the energy levels and the photophysics of PMI 1 and PMI-Pd 2 . Adapted from [ 59 ]. …”
Section: Figurementioning
confidence: 99%
“…[11] These emission characteristics of the PDI core matches well with the earlier reports of perylene chromophores. [9,12,26,27] Figure 1D shows FL spectra of PDIDA (in benzene) at various excitation wavelengths within the absorption range of PDIDA. The spectra reveal that PDIDA emission remains unaffected by the excitation wavelength indicating that the structure of the absorption spectrum is indeed due to the vibrational modes of the same electronically excited state.…”
Section: Absorption and Emission Characteristics: Pdida Electronic mentioning
confidence: 99%